PRISMA-combined Myeloperoxidase -463G/A gene polymorphism and coronary artery disease: A meta-analysis of 4744 subjects - Li, Yan-Yan; Wang, Hui; Qian, Jin; Kim, Hyun Jun; Wu, Jing-jing; Wang, Lian-sheng; Zhou, Chuan-wei; Yang, Zhi-Jian; Lu, Xin-Zheng (Medicine (Baltimore), 2017)
Myeloperoxidase (MPO) -463G/A gene polymorphism may be associated with an increased risk of developing coronary artery disease (CAD). Studies on the subject, however, do not provide a clear consensus. This meta-analysis was performed to explore the relationship between MPO gene -463G/A polymorphism and CAD risk. This meta-analysis combines data from 4744 subjects from 9 independent studies. By using fixed or random effect models, the pooled odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) were assessed. Our analysis found a significant association between MPO gene -463G/A polymorphism and CAD in the whole population under all genetic models: allelic (OR: 0.68, 95% CI: 0.54-0.85, P = 0.0009), recessive (OR: 0.41, 95% CI: 0.22-0.76, P = 0.005), dominant (OR: 0.682, 95% CI: 0.534-0.871, P = 0.002), homozygous (OR: 0.36, 95% CI: 0.16-0.79, P = 0.01), heterozygous genetic model (OR: 0.832, 95% CI: 0.733-0.945, P = 0.004), and additive (OR: 0.64, 95% CI: 0.46-0.90, P = 0.01), especially in the Chinese subgroup (P < 0.05). On the contrary, we found no such relationship in the non-Chinese subgroup (P > 0.05). The MPO gene -463G/A polymorphism is associated with CAD risk, especially within the Chinese population. The A allele of MPO gene -463G/A polymorphism might protect the people from suffering the CAD risk.